ETR 300 : Honey Bee Card / Nurasyikin Rosni ...[et al.] - Rosni, Nurasyikin; Mohd Idris, Sukmawati; Zainal Mohyin, Norazrina; Ahmad Walat, Siti Mafuza (2002)
Starting and preparing a new business involve considerable risk and effort overcomes the inertia against creating something new. In creating and growing a new business, the entrepreneur assumes the responsibilities and risks for each development and enjoys the corresponding reward. However, business people and government officials are interested in entrepreneurship is shown in the increasing research on the subject, the large number of college courses and seminar on topic and realization that this is an important topic for industrialized, development and once control economics.